Respuestas

  • Usuario de Brainly
2014-01-12T12:57:31+01:00
C) 7 - ( \frac{7}{6} - \frac{5}{6} )= 

7 - ( \frac{7-5}{6})=

7 - \frac{2}{6}=

 \frac{7*6}{6}  - \frac{2}{6}=

 \frac{42}{6}  - \frac{2}{6}=

 \frac{42-2}{6}=

 \frac{40}{6}=  \frac{20}{3}

Solución: 20/3


d) 1+ \frac{1}{3} -( \frac{1}{4} - \frac{1}{5} )=

1+ \frac{1}{3} -( \frac{1*5}{20} - \frac{1*4}{20} )=

1+ \frac{1}{3} -( \frac{5}{20} - \frac{4}{20} )=

1+ \frac{1}{3} -( \frac{5-4}{20} )=

1+ \frac{1}{3} - \frac{1}{20} =

1+ \frac{1*20}{60} - \frac{1*3}{60} =

 \frac{60}{60} + \frac{20}{60} - \frac{3}{60} =

 \frac{60+20-3}{60} =

 \frac{77}{60}

Solución: 77/60